A new deletion of 18q23 with few typical features of the 18q- syndrome. Issue 3 (March 1996) - Kohonen-Corish, M; Strathdee, G; Overhauser, J; McDonald, T; Jammu, V
Abstract : We report on a patient with a deletion of 18q23. At both 2 and 4 years of age, she displayed few of the facial features or other clinical features associated with the 18q- syndrome. Fluorescent in situ hybridisation and microsatellite marker and RFLP analysis were performed to characterise the extent of the deletion, and a terminal deletion of 18q23 was confirmed. The deleted region includes the gene for myelin basic protein, suggesting that hemizygosity of this gene does not invariably lead to mental and developmental delay. The clinical presentation of this patient suggests that either she is not deleted for the genes involved in the 18q- clinical phenotype or this patient represents one end of the spectrum of the clinical variability seen with 18q terminal deletions.